2020
DOI: 10.1002/ehf2.12718
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants compared to vitamin K antagonist for the management of left ventricular thrombus

Abstract: Aims Left ventricular (LV) thrombus is increasingly detected in patients with and without ischaemic heart disease due to the increased availability of cardiac magnetic resonance imaging. Risk factors include anterior ST elevation myocardial infarction, delayed reperfusion therapy, and non-ischaemic cardiomyopathy with severe LV systolic dysfunction. We aimed to report the characteristics and outcomes of patients with LV thrombus treated with either vitamin K antagonist (VKA) or direct oral anticoagulants (DOAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
188
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(210 citation statements)
references
References 38 publications
(62 reference statements)
19
188
1
2
Order By: Relevance
“…These results are consistent with results seen in some prior retrospective studies, where safety and e cacy of DOAC was comparable to warfarin for SSE prevention. [12,14,24,25] Our results are contrary to those of Robinson et al, who reported that treatment with DOACs was associated with a higher risk of SSE compared to warfarin. [13] It is important to note that in this study, DOAC group had more patients with traditional risk factors of stroke like history of prior SSE, hyperlipidemia, atrial brillation, apical thrombus and pedunculated thrombus which could have contributed to more SSE events.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are consistent with results seen in some prior retrospective studies, where safety and e cacy of DOAC was comparable to warfarin for SSE prevention. [12,14,24,25] Our results are contrary to those of Robinson et al, who reported that treatment with DOACs was associated with a higher risk of SSE compared to warfarin. [13] It is important to note that in this study, DOAC group had more patients with traditional risk factors of stroke like history of prior SSE, hyperlipidemia, atrial brillation, apical thrombus and pedunculated thrombus which could have contributed to more SSE events.…”
Section: Discussioncontrasting
confidence: 99%
“…Ten studies reported the occurrence of SSE [5][6][7][8][9][20][21][22][23][24][25] . The NOACs group and VKAs group did not show a significant difference in the risk of SSE (RR:0.96, 95% CI: 0.80-1.16, P = 0.69; I 2 = 0%, figure 3A).…”
Section: Stroke and Embolic Eventsmentioning
confidence: 99%
“…Eight studies reported the outcome of strokes 6,9,[19][20][21][22]24,25 . NOACs users showed lower risk of stroke compared with VKAs users (RR: 0.68, 95% CI: 0.68-1.00, P < 0.05, Figure 2B).…”
Section: Stroke and Embolic Eventsmentioning
confidence: 99%
See 2 more Smart Citations